2012
DOI: 10.1186/2049-1891-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Tissue expression and developmental regulation of chicken cathelicidin antimicrobial peptides

Abstract: Cathelicidins are a major family of antimicrobial peptides present in vertebrate animals with potent microbicidal and immunomodulatory activities. Four cathelicidins, namely fowlicidins 1 to 3 and cathelicidin B1, have been identified in chickens. As a first step to understand their role in early innate host defense of chickens, we examined the tissue and developmental expression patterns of all four cathelicidins. Real-time PCR revealed an abundant expression of four cathelicidins throughout the gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 29 publications
7
64
1
Order By: Relevance
“…Our analysis revealed that cathelicidins in local chickens are expressed in many organ and tissues, and these results were compatible with data reported in earlier studies (Achanta et al, 2012;Lynn et al, 2004;van Dijk et al, 2008;Wang et al, 2011;Xiao et al, 2006a;Zhao et al, 2001). In fact, CATH-1, -2 and -3 were shown to be expressed in a wide range of tissues, including the respiratory tract, gastrointestinal tract and multiple lymphoid organs.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our analysis revealed that cathelicidins in local chickens are expressed in many organ and tissues, and these results were compatible with data reported in earlier studies (Achanta et al, 2012;Lynn et al, 2004;van Dijk et al, 2008;Wang et al, 2011;Xiao et al, 2006a;Zhao et al, 2001). In fact, CATH-1, -2 and -3 were shown to be expressed in a wide range of tissues, including the respiratory tract, gastrointestinal tract and multiple lymphoid organs.…”
Section: Discussionsupporting
confidence: 95%
“…In fact, CATH-1, -2 and -3 were shown to be expressed in a wide range of tissues, including the respiratory tract, gastrointestinal tract and multiple lymphoid organs. Expression for all three genes was found to be high in lung, bone marrow, bursa and cecal tonsils (Achanta et al, 2012;Lynn et al, 2004;van Dijk et al, 2005). CATH-1 and -3 also showed high expression levels in the testis, and abundant expression for CATH-2 was found in the uropygial gland.…”
Section: Discussionmentioning
confidence: 92%
“…The expression level of CATH1, -2 and -3 was high in the lung and digestive tract, whereas the high expression of CATHB1 was identified in the bursa of Fabricius (Goitsuka et al, 2007;Achanta et al, 2012). Thus, it is likely that the differences in the expression profiles between CATHB1 and the other CATHs in the vagina resemble to the patterns of CATHs expression in other organs.…”
Section: Discussionmentioning
confidence: 87%
“…Broad spectrum antibiotics have a significant impact on the microbiota in the gastro-intestinal tract but their effect on the innate immunity of poultry in terms of antimicrobial peptides was not evaluated. CATH3 mRNA was described in many tissues of broilers (Achanta et al, 2012). In the cited study the highest expression levels were found in the lungs, caecal tonsils, proventriculus and the Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Administration of doxycycline did not provoke changes in the levels of CATH3 mRNA. Statistically significant up-regulation of mRNA of the studied gene was found in the jejunum of enrofloxacin Ross 308 chickens in com- (Achanta et al, 2012); H6PD -gene, encoding hexose-6-phosphate dehydrogenase; HPRT -gene, encoding hypoxanthine phosphoribosyltransferase 1; NCBI -the National Centre for Biotechnology Information; Ta -optimal annealing temperature.…”
Section: Resultsmentioning
confidence: 99%